The effect of earnings retention on common stock returns : An Applied study in Iraqi Stock Exchange - Maitham Rabie Hadi; Hosam Ali Hussain Fayad (Iraqi Journal for Administrative Sciences, 2024)
The concept of earnings retention one of the important concepts, because it contains important processes and procedures for decision-making related to it, so it requires balance sheet study of the company's and consider the plans investment and determine the necessary financing needs, and then carry out the distribution or retention of the earnings. Moreover, the distribution and retention policy has large effects beyond the limits of the tool for the distribution of the net surplus revenue for the costs. To reach that any difference in the rate of distributions have a major impact on stock prices, and changing stock prices in the financial market according to the latest information. This kind of changes in stock prices knows the hypothesis efficient market. Therefore, this study sought to test the effect of earnings retention on common stock returns as well as over the speed and response of common stock prices for information earnings retention. The sample study consisted of (8) banks. The limits study time of the has included years (2005-2013). The spatial boundaries were: the Iraq Stock Exchange, and adopted study two main hypotheses: 1- There is no correlation and effect statistically significant of between earnings retention and common stock returns. 2- Iraq Stock Exchange characterized by efficient semi-strong in responding to an event announcement earnings retention. In order to analyze the variables of the study and test hypotheses have been using a number of statistical methods and mathematical and financial. The study reached a number of conclusions, including: 1- There is relationship correlation and impact of statistically significant between the earnings retention and common stock returns and this is contrary with the hypothesis first study. 2- inefficiency Iraq Stock Exchange in the form semi-strong in connection its with response to an event announcement earnings retention and this is contrary with the hypothesis second study.